2017
DOI: 10.1002/hup.2630
|View full text |Cite
|
Sign up to set email alerts
|

Facial emotion recognition in schizophrenia: An exploratory study on the role of comorbid alcohol and substance use disorders and COMT Val158Met

Abstract: This study is the first to date examining the impact of AUDs/SUDs and COMT variants on FER in an epidemiologically representative sample of subjects with schizophrenia. Our findings do not suggest an additional impairment from comorbid AUDs/SUDs on FER among subjects with schizophrenia, whilst COMT Val158Met, though based on a limited sample, might have a role just among those without AUDs/SUDs. Based on our results, additional research is needed also exploring differential roles of various substances.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 34 publications
1
4
0
Order By: Relevance
“…Detection of facial emotions is the area of emotional behaviour that is best studied with respect to COMT genotype, although a variety of different experimental approaches have been employed. Our findings agree with most earlier studies showing no overall effect of COMT genotype on facial emotion detection ( Carrà et al, 2017 ; Defrancesco et al, 2011 ; Kempton et al, 2009 ; Soeiro-de-Souza et al, 2012 ; Tamm et al, 2016 ). We cannot rule out more subtle effects of COMT on detection of specific types of emotional information.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Detection of facial emotions is the area of emotional behaviour that is best studied with respect to COMT genotype, although a variety of different experimental approaches have been employed. Our findings agree with most earlier studies showing no overall effect of COMT genotype on facial emotion detection ( Carrà et al, 2017 ; Defrancesco et al, 2011 ; Kempton et al, 2009 ; Soeiro-de-Souza et al, 2012 ; Tamm et al, 2016 ). We cannot rule out more subtle effects of COMT on detection of specific types of emotional information.…”
Section: Discussionsupporting
confidence: 93%
“…Thus, while in some mouse models, lower COMT activity is associated with increased anxiety-like behaviours (Gogos et al, 1998;Papaleo et al, 2008), this is not seen for all COMT models (Barkus et al, 2016). Findings in human volunteers are also inconsistent: while some studies report exaggerated responses to negative stimuli and greater negative biases in processing emotional stimuli associated with the Met 158 , compared with the Val 158 , allele (Gohier et al, 2014;Gong et al, 2013;Montag et al, 2008), others have reported the opposite pattern (Weiss et al, 2007) or have found no genotype differences in emotional processing (Carrà et al, 2017;Defrancesco et al, 2011;Kempton et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…201), and in psychophysiological investigations (202). Deficits can be apparent in patients with multiple sclerosis (203), frontotemporal dementia (204206), schizophrenia (207210), ASD [Refs. (150, 151, 211) and forensic: Ref.…”
Section: Resultsmentioning
confidence: 99%
“…Secondly, patients enrolled in present study were treated with different antipsychotics for a long-term period, which could affect cognitive function in chronic patients with schizophrenia. Thirdly, we just examined a single genetic polymorphism effect on cognitive impairments of patients with schizophrenia, and other polymorphisms and genes interaction should be concerned [42]. Last but not the least, the RBANS has five domains including immediate memory, attention, language, visuospatial/ constructional, and delayed memory.…”
Section: Discussionmentioning
confidence: 99%